Performa Maturasi Siput Gonggong Laevistrombus turturella dengan Penyuntikan Sumber Hormon Gonadotropin Berbeda - Ryan Sukamto; Wiwin Kusuma Atmaja Putra; Muzahar (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
Overfishing makes the population of gonggong conch even smaller in their habitat. Its preservation can be maintained by cultivating gonggong conch, including by preparing mature gonads through induction using gonadotropim hormone. This study aims to obtain an effective type of hormone treatment in accelerating the maturation process of the gonggong conch gonads. This research was conducted in April - July 2020 at the Laboratory of the Faculty of Maritime Science and Fisheries, Raja Ali Haji Maritime University, Tanjungpinang, Kepri Province. The method used is a completely randomized design (CRD) with 4 treatments and 3 replications, injection treatment NaCl 0,5µL/head (K), injection treatment oodev® 0,5µL/head (PA), injection treatment PG600® 0,5µL/head (PB), injection treatment oodev® 0,25 µL + PG600® 0,25 µL/head (PC). The results showed that the highest GSI value is PC treatment (0.12±0.36%). Effective treatment in accelerating the process of maturing of gonggong conch gonads is a PC treatment because it reaches TKG II through the histology result ogf gonad. The highest absolute weight growth of the gonggong conch was the PC treatment (0.07±0.01 g). The highest growth length of the gonggong conch was the PC treatment (0.83±0.23cm).